Estimating the Impacts of Bus Stops and Transit Signal Priority on Intersection Operations: Queuing and Variational Theory Approach. Issue 1 (2017) - Wu, Kan; Guler, S. Ilgin; Gayah, Vikash V.
Transit signal priority (TSP) can be used to improve bus operations at signalized intersections, often to the detriment of general car traffic. However, the impacts of TSP treatments applied to intersections with nearby bus stop locations are currently unknown. This paper quantifies changes in intersection capacity, car delay, and bus delay when priority is provided to buses that dwell at near- or farside bus stop locations through green extension or red truncation. Variational and kinematic wave theories are used to estimate car capacity and bus delay for oversaturated traffic conditions; queuing theory is used to estimate car and bus delays for undersaturated conditions. Numerical analyses are conducted to explore the impacts on various bus stop locations and bus dwell time durations. These results illustrate clear trade-offs between reduced bus delays and increased car delays or reduced intersection capacities that can be quantified with the proposed method. The results also reveal that the effects of TSP vary dramatically with bus dwell times for a given bus stop location. The proposed method and associated results can be used to implement TSP strategies to meet the specific needs of local agencies.